The product manager's handbook, fourth edition - Gorchels, Linda (McGraw-Hill, 2012)
Examining current market-leading companies; the latest research findings; and evolving customer perceptions; this indispensable resource provides the tools you need to design; produce; and market winning productsand beat the competition at every turn. --